Seaport adaptation to climate change-related disasters: terminal operator market structure and inter- and intra-port coopetition - Wang, Kun; Yang, Hangjun; Zhang, Anming (Spatial economic analysis, 2020)
With the prevalence of global terminal operators in port operation, the market structure of terminal operator companies (TOCs) becomes more important in shaping intra- and inter-port competition and cooperation (i.e., coopetition). The port adaptation investment to climate change-related disaster might also be affected by such TOC intra- and inter-port coopetition. This paper examines analytically how the TOC market structure could affect ports' adaptation investment. More specifically, it considers two landlord-type ports within a region that compete with each other. The two ports are subject to uncertain disaster threats and have an asymmetric number of TOCs. The analytical and numerical results suggest that more TOCs at the own port and the competing port have opposite impacts on the port's adaptation investment. An inter-port TOC joint venture would decrease the adaptation at both ports. Moreover, the TOC market structure is found to moderate the effect of disaster uncertainty on port adaptation. That is, TOC intra- and inter-port coopetition can strengthen or weaken ports' sensitivity to disaster occurrence uncertainty. Finally, the regional welfare is found to increase monotonely with the two ports' total adaptation. It is suggested that the regulators encourage new TOC entries while restricting inter-port TOC joint ventures. The cases with heterogeneous disaster uncertainties at the two ports are also examined.